Impact of Teaching Beliefs and Socioemotional Competencies on theIntegration of ICT by Religion Teachers - Cartagena-Beteta, Mario Armando (2025)
Objective. This study is part of a doctoral thesis and examines the impact of teaching beliefs and socioemotional competencies on the integration of information and communication technologies (ICT) in religious education, considering gender and experience. Methodology. A causal-comparative design with a quantitative approach was employed. The sample comprised 303 public school teachers from Lima, Peru, who responded to three instruments aligned with the study variables. Multiple linear regression and statistical comparison tests were conducted to establish differences between groups. Findings. The results confirm that teachers’ personal characteristics (beliefs and socioemotional competencies) positively predict ICT integration. However, beliefs have a stronger influence. Furthermore, experience contributes to the structuring of beliefs and emotion management, particularly among teachers with 11 and 20 years of service, in contrast to gender. Applications. The study is useful for decision-making in teacher education and training, as well as in evaluating the field of religious education as a subject of research.